Individual Muscle Hypertrophy and Strength Responses to High vs. Low Resistance Training Frequencies - Damas, Felipe; Barcelos, Cintia; Nóbrega, Sanmy R; Ugrinowitsch, Carlos; Lixandrão, Manoel E; Santos, Lucas M E D; Conceição, Miguel S; Vechin, Felipe C; Libardi, Cleiton A (Journal of strength and conditioning research, 2019)
Damas, F, Barcelos, C, Nóbrega, SR, Ugrinowitsch, C, Lixandrão, ME, Santos, LMEd, Conceição, MS, Vechin, FC, and Libardi, CA. Individual muscle hypertrophy and strength responses to high vs. low resistance training frequencies. J Strength Cond Res 33(4): 897-901, 2019-The aim of this short communication was to compare the individual muscle mass and strength gains with high (HF) vs. low (LF) resistance training (RT) frequencies using data from our previous study. We used a within-subject design in which 20 subjects had one leg randomly assigned to HF (5× per week) and the other to LF (2 or 3× per week). Muscle cross-sectional area and 1 repetition maximum were assessed at baseline and after 8 weeks of RT. HF showed a higher 8-week accumulated total training volume (TTV) (p < 0.0001) compared with LF. Muscle cross-sectional area and 1 repetition maximum values increased significantly and similarly for HF and LF protocols (p > 0.05). This short communication highlights that some individuals showed greater muscle mass and strength gains after HF (31.6 and 26.3% of individuals, respectively), other had greater gains with LF (36.8 and 15.8% of individuals, respectively), and even others showed similar responses between HF and LF, regardless of the consequent higher or lower TTV resulted from HF and LF, respectively. Importantly, individual manipulation of RT frequency can improve the intrasubject responsiveness to training, but the effect is limited to each individual's capacity to respond to RT. Finally, individual response to different frequencies and resulted TTV does not necessarily agree between muscle hypertrophy and strength gains.